Ferrous activated persulfate sustained-release material as well as preparation method and application thereof

By revolvingly bonded ferrous ferrous persulfate sustained release materials, the problem of excessively fast persulfate reaction speed in the prior art is solved, the coordinated release and activation of ferrous sulfate and sodium persulfate are achieved, and the groundwater is significantly improved Effect and persistence of pollution repair.

CN119390227APending Publication Date: 2025-02-07CHINA UNIV OF MINING & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411751922.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, persulfate reacts too fast in the groundwater environment, making it difficult to synchronously activate and fully utilize, which in turn leads to poor groundwater pollution repair effect.

Method used

Ferrous activated persulfate sustained release material, which uses citric acid and sodium carboxymethylcellulose to control the release rate to achieve ferrous sulfate and persulfate sustained release material units. Cooperative release and activation of sodium.

Benefits of technology

The problem of excessive consumption of agents and inability to synchronously activate is overcome, and long-term and stable degradation of organic pollutants in groundwater has been achieved, significantly extending the action time of the agents and improving utilization efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390227A_ABST
    Figure CN119390227A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of underground water treatment, and particularly relates to a ferrous activated persulfate slow-release material as well as a preparation method and application thereof. The ferrous activated persulfate sustained-release material is obtained by alternately bonding ferrous sulfate sustained-release material units and persulfate sustained-release material units in a mass ratio of 1: (1-1.5) along the length direction; wherein the ferrous sulfate slow-release material is formed by mixing and solidifying a first coagulator, ferrous sulfate, citric acid and first sodium carboxymethyl cellulose, and the persulfate slow-release material is formed by mixing and solidifying a second coagulator, sodium persulfate and second sodium carboxymethyl cellulose; the mass ratio of the ferrous sulfate to the citric acid to the sodium persulfate is 1: (0.5-1): (0.15-7.5). Synergistic long-acting release of the activating agents ferrous sulfate and persulfate is achieved by combining a slow release technology, the problems that in the prior art, medicament consumption is too fast, and synchronous activation cannot be achieved are solved, and organic pollutants in underground water can be stably degraded in a long-acting mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of groundwater treatment, and in particular relates to a ferrous activated persulfate slow-release material and a preparation method and application thereof. Background Art

[0002] Organic pollution in groundwater is hidden, persistent and irreversible. Once groundwater is polluted, it is not easy to detect. Drinking contaminated groundwater will cause direct harm to human health. Due to the complexity of the groundwater system, groundwater pollution remediation faces many challenges, including large capital investment, long cycle and unsatisfactory results.

[0003] In-situ chemical oxidation technology has become one of the commonly used technologies for groundwater organic pollution remediation due to its advantages such as good removal effect, low environmental interference and low investment cost, and is currently a hot topic of research. Persulfate, as one of the commonly used oxidants in ISCO, is more efficient and stable than other types of oxidants. It also has the advantages of a wide pH value application range, high redox potential after activation, and more thorough degradation of pollutants.

[0004] There are many ways to activate persulfate, among which transition metal activation is the most common. Transition metal activation of persulfate does not require additional energy input and can be carried out quickly at room temperature and pressure. As a transition metal, Fe has been widely studied and applied to the activation of persulfate due to its high content in the natural environment, low cost, and environmental friendliness.

[0005] Currently, persulfate and activators are usually injected directly in the form of liquid agents. However, due to their rapid reaction speed in groundwater environments, persulfate is difficult to be activated and fully utilized simultaneously, resulting in poor remediation effects. Summary of the invention

[0006] In order to solve the above problems, the present invention provides a ferrous sulfate activated persulfate sustained-release material and its preparation method and application. The activator ferrous sulfate and persulfate are released in coordination, which overcomes the problem of too fast consumption of the agent and inability to activate synchronously in the prior art, and can degrade organic pollutants in groundwater in a long-term and stable manner.

[0007] The present invention solves the above technical problems through the following technical solutions.

[0008] One of the purposes of the present invention is to provide a ferrous activated persulfate slow-release material, which comprises a ferrous sulfate slow-release material unit and a persulfate slow-release material unit. Along the length direction of the ferrous activated persulfate slow-release material, the ferrous sulfate slow-release material unit and the persulfate slow-release material unit are alternately bonded at a mass ratio of 1:1 to 1.5 to obtain the ferrous activated persulfate slow-release material; wherein the ferrous sulfate slow-release material is formed by mixing and coagulating a first coagulant, ferrous sulfate, citric acid and a first sodium carboxymethyl cellulose, and the persulfate slow-release material is formed by mixing and coagulating a second coagulant, sodium persulfate and a second sodium carboxymethyl cellulose; and the mass ratio of ferrous sulfate, citric acid and sodium persulfate is 1:0.5 to 1:0.15 to 7.5.

[0009] Furthermore, the mass ratio of ferrous sulfate to the first coagulant is 0.6-3:1, and the mass ratio of the first sodium carboxymethyl cellulose to ferrous sulfate is 1:100.

[0010] Furthermore, the mass ratio of sodium persulfate to the second coagulant is 0.5-3:1, and the mass ratio of the second sodium carboxymethyl cellulose to sodium persulfate is 1:100.

[0011] Furthermore, the ferrous sulfate activated persulfate sustained-release material is a cylindrical structure with a diameter of 10 mm to 30 mm, and the lengths of the ferrous sulfate sustained-release material unit and the persulfate sustained-release material unit are both 25 mm to 75 mm.

[0012] Furthermore, the first coagulant and the second coagulant are both paraffin wax, the melting point of paraffin wax is 48°C to 50°C, and the density is 0.8 g / cm 3 .

[0013] Furthermore, the particle size of the ferrous sulfate is 100-120 mesh; the particle size of the first sodium carboxymethyl cellulose and the second sodium carboxymethyl cellulose are both 100 mesh.

[0014] The second object of the present invention is to provide a method for preparing the above-mentioned ferrous iron activated persulfate sustained-release material, comprising the following steps:

[0015] S1. Heat the first coagulant until it melts, then add ferrous sulfate, citric acid and the first sodium carboxymethyl cellulose, mix well, and solidify to obtain a ferrous sulfate sustained-release material unit.

[0016] S2. Heat the second coagulant until it melts, then add sodium persulfate and the second sodium carboxymethyl cellulose, mix well, and solidify to obtain a sodium persulfate sustained-release material unit.

[0017] S3. Alternately bonding the ferrous sulfate slow-release material units and the sodium persulfate slow-release material units with a binder to obtain a ferrous sulfate activated persulfate slow-release material.

[0018] Furthermore, the binder is paraffin.

[0019] The third object of the present invention is to provide the application of the above-mentioned ferrous iron activated persulfate slow-release material in in-situ oxidation remediation of groundwater.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The present invention combines a persulfate system and its activation and sustained-release technology to provide a ferrous-activated persulfate sustained-release material that simultaneously releases ferrous sulfate and sodium persulfate, wherein a first coagulant is coated with ferrous sulfate, citric acid and a first sodium carboxymethyl cellulose to form a ferrous sulfate sustained-release material unit, and a second coagulant is coated with sodium persulfate and a second sodium carboxymethyl cellulose to form a sodium persulfate sustained-release material unit. Along the length direction of the ferrous-activated persulfate sustained-release material, the ferrous sulfate sustained-release material unit and the persulfate sustained-release material unit are alternately bonded, and the sodium carboxymethyl cellulose is used to form a ferrous sulfate sustained-release material unit. The dispersion uniformity of each raw material is increased, and the prepared ferrous activated persulfate slow-release material forms a complex with citric acid and part of ferrous sulfate, and the release rate of ferrous sulfate is controlled by the slow-release effect of the complex in cold water. The release rate, release life and release percentage of sodium persulfate are controlled by citric acid and ferrous sulfate, so as to achieve the purpose of synchronous release and activation with sodium persulfate, realize the coordinated release of the activator ferrous sulfate and persulfate, overcome the problem of too fast agent consumption and failure of synchronous activation in the prior art, and can degrade organic pollutants in groundwater in a long-term and stable manner.

[0022] (2) The present invention adjusts the ratio of the first coagulant (paraffin), ferrous sulfate and citric acid to control the release rate of ferrous sulfate in the sustained-release material unit, adjusts the ratio of the second coagulant and sodium persulfate, and the material diameter to control the release rate of sodium persulfate in the sustained-release material, and then effectively releases the life span and the percentage of release, so as to achieve the purpose of efficiently activating sodium persulfate to degrade organic pollutants in groundwater.

[0023] (3) The present invention adopts a sodium persulfate persulfate system, using sodium persulfate as an oxidant to degrade organic pollutants by activating ferrous iron to produce highly oxidizing reactive oxygen species, and by using citric acid to improve the pH value of the water layer, promoting ferrous iron to activate reactive oxygen species, and enhancing the bioremediation potential of organic pollution in groundwater.

[0024] (4) The present invention prepares a ferrous activated persulfate sustained-release material with a cylindrical structure by alternately bonding ferrous sulfate sustained-release material units and sodium persulfate sustained-release material units along the length direction of the ferrous activated persulfate sustained-release material through paraffin. The slow dissolution and release and synchronous activation of the active substance (sodium persulfate or ferrous sulfate) coated therein are achieved through a coagulant, thereby significantly extending the action time of the agent, achieving the synergistic and long-term release of the activator ferrous sulfate and persulfate, and improving the utilization efficiency of the agent. The problems of large agent loss, poor effect sustainability and pollution rebound when persulfate is directly used are effectively solved, and a new solution is provided for in situ chemical oxidation remediation and long-term management of organically contaminated groundwater. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a physical picture of the ferrous iron activated persulfate sustained-release material prepared in the present invention.

[0026] Figure 2 This is a degradation curve diagram of benzene of the sustained-release materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1.

[0027] Figure 3 Surface microstructure diagram of the cylindrical ferrous sulfate sustained-release material before and after release in Example 1 of the present invention. Figure 3 a and b are SEM images of the surface of the cylindrical ferrous sulfate sustained-release material before and after release at 100 times magnification, and c and d are SEM images of the surface before and after release at 500 times magnification.

[0028] Figure 4 This is a microscopic structure diagram of the material surface of the cylindrical ferrous sulfate sustained-release material before and after release in Example 1 of the present invention. Figure 4 a and b are SEM images of the surface of the cylindrical ferrous sulfate sustained-release material before and after release at 100 times magnification, and c and d are SEM images of the surface before and after release at 500 times magnification.

[0029] Figure 5 The release curve of ferrous sulfate in the sustained-release materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 is shown.

[0030] Figure 6 The release curve of sodium persulfate in the sustained-release materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 is shown.

[0031] Figure 7 This is a diagram showing the influence of Fick diffusion inside the matrix on the release of the cylindrical ferrous sulfate sustained-release material FeSO4·7H2O in Example 1 of the present invention.

[0032] Figure 8This is a performance diagram of the slow-release material prepared in Examples 1 to 4 of the present invention and Comparative Example 1 in simulating the oxidation degradation of benzene in an aquifer. Figure 8 In the figure, a is the performance diagram for the degradation of benzene, and b is the performance diagram for the degradation of phenanthrene.

[0033] Fig. 9 This is a performance diagram of the slow-release material prepared in Example 1 of the present invention simulating the degradation of benzene in groundwater. Fig. 9 Where a is the overall degradation rate of benzene at 5 days, b is the overall degradation rate of benzene at 10 days, and c is the overall degradation rate of benzene at 20 days. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.

[0036] In the prior art, persulfate and activator are usually directly injected in the form of liquid agents, but due to the high reaction speed in the groundwater environment, persulfate is difficult to be activated and fully utilized simultaneously, resulting in poor remediation effect. In order to solve this problem, it is usually necessary to inject excessive agents to improve the remediation effect, which will increase costs and have adverse effects on the groundwater environment.

[0037] Therefore, the problem of how to efficiently utilize and activate persulfate is to prepare a slow-release material that can synchronously release activators and oxidants in underground aquifers for a long time and stably for in-situ chemical oxidation remediation to overcome the defects of existing remediation technology, which is of great significance for the treatment of organically contaminated groundwater.

[0038] Based on the above problems, the present invention provides a ferrous activated persulfate slow-release material, which comprises a ferrous sulfate slow-release material unit and a persulfate slow-release material unit. Along the length direction of the ferrous activated persulfate slow-release material, the ferrous sulfate slow-release material unit and the persulfate slow-release material unit are alternately bonded at a mass ratio of 1:1 to 1.5 to obtain the ferrous activated persulfate slow-release material; wherein, the ferrous sulfate slow-release material is formed by mixing and coagulating a first coagulant, ferrous sulfate, citric acid and a first sodium carboxymethyl cellulose, and the persulfate slow-release material is formed by mixing and coagulating a second coagulant, sodium persulfate and a second sodium carboxymethyl cellulose; and the mass ratio of ferrous sulfate, citric acid and sodium persulfate is 1:0.5 to 1:0.15 to 7.5.

[0039] The invention combines a persulfate system and its activation and sustained-release technology to provide a ferrous activated persulfate sustained-release material capable of synchronously slow-releasing ferrous sulfate and sodium persulfate. A first coagulant is used to coat ferrous sulfate, citric acid and a first sodium carboxymethyl cellulose to form a ferrous sulfate sustained-release material unit, and a second coagulant is used to coat sodium persulfate and a second sodium carboxymethyl cellulose to form a sodium persulfate sustained-release material unit. Along the length direction of the ferrous activated persulfate sustained-release material, the ferrous sulfate sustained-release material unit and the persulfate sustained-release material unit are alternately bonded, and the sodium carboxymethyl cellulose is used to increase the dispersion uniformity of each raw material. The prepared ferrous activated persulfate sustained-release material is The iron-activated persulfate slow-release material forms a complex with citric acid and part of ferrous sulfate, and controls the release rate of ferrous sulfate through the slow-release effect of the complex in cold water. The release rate, release life and release percentage of sodium persulfate are controlled by citric acid and ferrous sulfate, so as to achieve the purpose of synchronous release and activation with sodium persulfate. It is used for in-situ chemical oxidation remediation of organically contaminated groundwater and long-term risk management projects, realizes the coordinated release of the activator ferrous sulfate and sodium persulfate persulfate, overcomes the problem of too fast agent consumption and inability to be activated synchronously in the prior art, and can degrade organic pollutants in groundwater in a long-term and stable manner.

[0040] In some specific embodiments, the mass ratio of ferrous sulfate to the first coagulant is 0.6 to 3: 1, the mass ratio of ferrous sulfate to citric acid is 1: 0.5 to 1, and the mass ratio of the first sodium carboxymethyl cellulose to ferrous sulfate is 1: 100. It should be noted that the present invention controls the release rate, effective release life and release percentage of ferrous sulfate in the sustained-release material by adjusting the ratio of the first coagulant (paraffin), ferrous sulfate and citric acid, so as to achieve the purpose of efficiently activating sodium persulfate to degrade organic pollutants in groundwater. Preferably, the mass ratio of ferrous sulfate to the first coagulant is 2: 3 or 1: 1, the mass ratio of ferrous sulfate to citric acid is 1: 0.5, when the mass ratio of ferrous sulfate to paraffin is lower than 0.6: 1, the release rate of ferrous sulfate is too slow, and the ferrous sulfate in the sustained-release material is unevenly distributed in paraffin; when the mass ratio of ferrous sulfate to the first coagulant is higher than 3: 1, the material cannot be prepared and formed.

[0041] In some specific embodiments, the mass ratio of sodium persulfate to the second coagulant is 0.5 to 3:1, and the mass ratio of the second sodium carboxymethyl cellulose to sodium persulfate is 1:100. The present invention can control the release rate, effective release life and release percentage of sodium persulfate in the sustained-release material by adjusting the ratio of the second coagulant to sodium persulfate and the material diameter to achieve the effect of stable and long-term release of sodium persulfate. Preferably, the mass ratio of sodium persulfate to the second coagulant is 2:1. When the mass ratio of sodium persulfate to paraffin is lower than 0.5:1, the release rate of sodium persulfate is too slow, and sufficient sodium persulfate cannot be provided in practical application; when the mass ratio of sodium persulfate to paraffin is higher than 3:1, the "sudden release" phenomenon is serious; when the mass ratio of sodium persulfate to paraffin is 2:1, the release rate is appropriate, the release is stable, and the release life is long.

[0042] It should be noted that the present invention uses sodium persulfate as a persulfate system, wherein sodium persulfate itself is a strong oxidant, but in its original state, the oxidizing ability is relatively weak, and it is necessary to undergo activation treatment to significantly improve its oxidizing performance. Sodium persulfate is used as an oxidant, and strong oxidizing active oxygen species are generated by ferrous activation to degrade organic pollutants, and the pH value of the water layer can be improved by citric acid, promoting the activation of active oxygen species by ferrous peroxide, and the bioremediation potential of organic pollution in groundwater can be enhanced.

[0043] In some specific embodiments, the ferrous sulfate activated persulfate sustained-release material is a cylindrical structure with a diameter of 10 mm to 30 mm, and the lengths of the ferrous sulfate sustained-release material unit and the persulfate sustained-release material unit are both 25 mm to 75 mm. Preferably, along the length direction of the ferrous activated persulfate slow-release material, the ferrous sulfate slow-release material units and the persulfate slow-release material units are alternately bonded in a mass ratio of 1:1 to form a cylindrical structure of the ferrous activated persulfate slow-release material, the diameter of the cylindrical structure of the ferrous activated persulfate slow-release material is 22 mm, and the lengths of the ferrous sulfate slow-release material units and the persulfate slow-release material units are both 50 mm. The slow dissolution and release and synchronous activation of the active substance (sodium persulfate or ferrous sulfate) coated therein are achieved by the paraffin coagulant, thereby significantly extending the action time of the agent, achieving the coordinated long-term release of the activator ferrous sulfate and sodium persulfate persulfate, improving the utilization efficiency of the agent, and effectively solving the problems of large agent loss, poor effect sustainability and pollution rebound when persulfate is directly applied, providing a new solution for in situ chemical oxidation remediation and long-term control of organically contaminated groundwater.

[0044] In some specific embodiments, the first coagulant and the second coagulant are both paraffin wax, the melting point of paraffin wax is 48°C to 50°C, and the density is 0.8 g / cm 3 Paraffin is a solid mixture of higher alkanes with a molecular formula of C n H 2n+2 , where n = 20 to 40. It is usually a white waxy solid with a slight odor, does not react with common chemical reagents, has a melting point of 47°C to 65°C, and a density of 0.8 g / cm 3 The use of paraffin with a lower melting point (48°C to 50°C) as the coating material reduces the loss of reagents caused by the oxidation of ferrous sulfate and the high-temperature decomposition of sodium persulfate during the preparation process.

[0045] In some specific embodiments, the particle size of the ferrous sulfate is 100-120 mesh; the particle size of the first sodium carboxymethyl cellulose and the second sodium carboxymethyl cellulose are both 100 mesh.

[0046] The preparation method of the above-mentioned ferrous iron activated persulfate sustained-release material comprises the following steps:

[0047] S1. Heat the first coagulant until it melts, then add ferrous sulfate, citric acid and the first sodium carboxymethyl cellulose, mix well, and solidify to obtain a ferrous sulfate sustained-release material unit.

[0048] S2. Heat the second coagulant until it melts, then add sodium persulfate and the second sodium carboxymethyl cellulose, mix well, and solidify to obtain a sodium persulfate sustained-release material unit.

[0049] S3. Alternately bonding the ferrous sulfate slow-release material units and the sodium persulfate slow-release material units with a binder to obtain a ferrous sulfate activated persulfate slow-release material.

[0050] The material used in the present invention is environmentally friendly, has a simple and easy preparation process, can adjust the preparation size according to actual needs, is easy to deploy, replace and maintain, and can be used in organically contaminated groundwater remediation projects with different organic pollution levels and geological conditions.

[0051] In some specific embodiments, the binder is paraffin. It should be noted that the binder used in the present invention is only used to bind the ferrous sulfate sustained-release material and the sodium persulfate sustained-release material to form an alternating cylindrical structure.

[0052] The present invention also provides the application of the above-mentioned ferrous activated persulfate slow-release material in in-situ oxidation remediation of groundwater. In some specific embodiments, the release percentage of ferrous sulfate in the ferrous activated persulfate slow-release material is 79% to 90%, and the release percentage of sodium persulfate is 80% to 97%. In some specific embodiments, the effective release life of the cylindrical ferrous activated persulfate slow-release material is 70d to 100d. The present invention realizes the synergistic long-term release of the activator ferrous sulfate and persulfate by combining the slow-release technology, effectively solving the problems of large agent loss, poor effect sustainability and pollution rebound when persulfate is directly applied, and provides a new solution for in-situ chemical oxidation remediation and long-term management of organic contaminated groundwater.

[0053] The invention is further described below through specific examples.

[0054] Example 1

[0055] A method for preparing a ferrous iron activated persulfate sustained-release material comprises the following steps:

[0056] S1. Paraffin wax (melting point 48℃~50℃, density about 0.8g / cm 3 ) is heated to melt in a constant temperature water bath at 65° C., and then ferrous sulfate with a particle size of 100 mesh, citric acid and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of ferrous sulfate to paraffin is 1:1, the mass ratio of sodium carboxymethyl cellulose to ferrous sulfate is 1:100, and the mass ratio of ferrous sulfate to citric acid is 1:0.5, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical ferrous sulfate sustained-release material unit, wherein the cylindrical ferrous sulfate sustained-release material unit has a diameter of 2.2 cm and a length of 5 cm.

[0057] S2, paraffin wax (melting point 48 ℃ ~ 50 ℃, density about 0.8g / cm3 ) is heated to melt in a constant temperature water bath at 65° C., and then sodium persulfate with a particle size of 100 mesh and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of sodium persulfate to paraffin is 2:1, and the mass ratio of sodium carboxymethyl cellulose to sodium persulfate is 1:100, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical sodium persulfate sustained-release material unit, wherein the cylindrical sodium persulfate sustained-release material unit has a diameter of 2.2 cm and a length of 5 cm.

[0058] S3, along the length direction of the ferrous sulfate activated persulfate sustained-release material, the ferrous sulfate sustained-release material unit and the sodium persulfate sustained-release material unit are alternately bonded twice with paraffin wax to obtain the ferrous sulfate activated persulfate sustained-release material. Figure 1 As shown, the ferrous iron activated persulfate sustained-release material has a diameter of 2.2 cm and a length of 20 cm.

[0059] Example 2

[0060] A method for preparing a ferrous iron activated persulfate sustained-release material comprises the following steps:

[0061] S1. Paraffin wax (melting point 48℃~50℃, density about 0.8g / cm 3 ) is heated to melt in a constant temperature water bath at 65° C., and then ferrous sulfate with a particle size of 100 mesh, citric acid and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of ferrous sulfate to paraffin is 2:1, the mass ratio of sodium carboxymethyl cellulose to ferrous sulfate is 1:100, and the mass ratio of ferrous sulfate to citric acid is 1:0.1, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical ferrous sulfate sustained-release material unit, wherein the cylindrical ferrous sulfate sustained-release material unit has a diameter of 2.2 cm and a length of 5 cm.

[0062] S2, paraffin wax (melting point 48 ℃ ~ 50 ℃, density about 0.8g / cm 3 ) is heated to melt in a constant temperature water bath at 65° C., and then sodium persulfate with a particle size of 100 mesh and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of sodium persulfate to paraffin is 2:1, and the mass ratio of sodium carboxymethyl cellulose to sodium persulfate is 1:100, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical sodium persulfate sustained-release material unit, wherein the cylindrical sodium persulfate sustained-release material unit has a diameter of 2.2 cm and a length of 5 cm.

[0063] S3. Along the length direction of the ferrous sulfate activated persulfate sustained-release material, the ferrous sulfate sustained-release material unit and the sodium persulfate sustained-release material unit are alternately bonded twice with paraffin wax to obtain a ferrous sulfate activated persulfate sustained-release material with a diameter of 20 mm.

[0064] Example 3

[0065] A method for preparing a ferrous iron activated persulfate sustained-release material comprises the following steps:

[0066] S1. Paraffin wax (melting point 48℃~50℃, density about 0.8g / cm 3 ) is heated to melt in a constant temperature water bath at 65° C., and then ferrous sulfate with a particle size of 100 mesh, citric acid and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of ferrous sulfate to paraffin is 2:3, the mass ratio of sodium carboxymethyl cellulose to ferrous sulfate is 1:100, and the mass ratio of ferrous sulfate to citric acid is 1:1, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical ferrous sulfate sustained-release material unit, wherein the cylindrical ferrous sulfate sustained-release material unit has a diameter of 2.2 cm and a length of 5 cm.

[0067] S2, paraffin wax (melting point 48 ℃ ~ 50 ℃, density about 0.8g / cm 3 ) is heated to melt in a constant temperature water bath at 65° C., and then sodium persulfate with a particle size of 100 mesh and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of sodium persulfate to paraffin is 2:1, and the mass ratio of sodium carboxymethyl cellulose to sodium persulfate is 1:100, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical sodium persulfate sustained-release material unit, wherein the cylindrical sodium persulfate sustained-release material unit has a diameter of 2.2 cm and a length of 5 cm.

[0068] S3. Along the length direction of the ferrous sulfate activated persulfate sustained-release material, the ferrous sulfate sustained-release material and the sodium persulfate sustained-release material are alternately bonded twice with paraffin wax to obtain a ferrous sulfate activated persulfate sustained-release material with a diameter of 20 mm.

[0069] Example 4

[0070] A method for preparing a ferrous iron activated persulfate sustained-release material comprises the following steps:

[0071] S1. Paraffin wax (melting point 48℃~50℃, density about 0.8g / cm 3) is heated to melt in a constant temperature water bath at 65° C., and then ferrous sulfate with a particle size of 100 mesh, citric acid and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of ferrous sulfate to paraffin is 3:1, the mass ratio of sodium carboxymethyl cellulose to ferrous sulfate is 1:100, and the mass ratio of ferrous sulfate to citric acid is 1:1, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical ferrous sulfate sustained-release material unit, wherein the cylindrical ferrous sulfate sustained-release material unit has a diameter of 2.2 cm and a length of 5 cm.

[0072] S2, paraffin wax (melting point 48 ℃ ~ 50 ℃, density about 0.8g / cm 3 ) is heated to melt in a constant temperature water bath at 65° C., and then sodium persulfate with a particle size of 100 mesh and sodium carboxymethyl cellulose with a particle size of 100 mesh are added, wherein the mass ratio of sodium persulfate to paraffin is 2:1, and the mass ratio of sodium carboxymethyl cellulose to sodium persulfate is 1:100, and the mixture is fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture is quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, cooled naturally to room temperature, and demolded to obtain a cylindrical sodium persulfate sustained-release material, wherein the cylindrical ferrous sulfate sustained-release material has a diameter of 2.2 cm and a length of 5 cm.

[0073] S3. Along the length direction of the ferrous sulfate activated persulfate sustained-release material, the ferrous sulfate sustained-release material unit and the sodium persulfate sustained-release material unit are alternately bonded twice with paraffin wax to obtain a ferrous sulfate activated persulfate sustained-release material with a diameter of 30 mm.

[0074] Comparative Example 1

[0075] A method for preparing a persulfate sustained-release material comprises the following steps:

[0076] S1. Paraffin wax (melting point 48℃~50℃, density about 0.8g / cm 3 ) heated to melt in a constant temperature water bath at 65° C., then added sodium persulfate with a particle size of 100 mesh, the mass ratio of sodium persulfate to paraffin was 2:1, and the mass ratio of sodium carboxymethyl cellulose to sodium persulfate was 1:100, and fully mixed and stirred to obtain a semi-solid mixture; the semi-solid mixture was quickly poured into a cylindrical mold sprayed with an oily release agent, shaken to eliminate residual bubbles, naturally cooled to room temperature, and demolded to obtain a cylindrical sodium persulfate sustained-release material unit, the diameter of the cylindrical ferrous sulfate sustained-release material unit was 2.2 cm and the length was 5 cm.

[0077] S3. Four cylindrical sodium persulfate sustained-release material units were bonded with paraffin along the length direction to obtain a sodium persulfate sustained-release material with a diameter of 20 mm, named PDS@PW.

[0078] The results of the structure and performance tests on the sustained-release materials prepared in Examples 1 to 4 and Comparative Example 1 are as follows:

[0079] The slow-release materials prepared in Examples 1 to 4 and Comparative Example 1 were used to oxidize and degrade benzene in water, and the degradation effect and long-term effect of the slow-release materials on benzene and phenanthrene in water were investigated. The initial concentration of benzene in water was 30 mg / L, and the specific implementation process was as follows:

[0080] Before the sustained-release materials prepared in Examples 1 to 4 and Comparative Example 1 are placed in an aqueous solution, the surface of the material is polished with sandpaper to remove the residual release agent on the surface. It is placed in a sealed bottle containing 1000mL of pollutant benzene aqueous solution and placed in a dark environment at room temperature to statically degrade benzene and phenanthrene in water. A total of 6 groups are set up, with only paraffin added as a blank control group, and three parallel experiments are set up in each group. The time when the sustained-release material is placed is recorded as the starting time point of the reaction, and a disposable syringe is used to sample and test at specific time intervals to monitor the degradation efficiency of benzene within 15 days. The concentration of benzene and phenanthrene in the sample is tested using an Agilent 6890N gas chromatograph with headspace sampling.

[0081] Figure 2 The following is a graph showing the degradation of benzene by the sustained-release materials prepared in Examples 1 to 4 and Comparative Example 1 of the present invention. Figure 2 As described above, after 15 days of continuous sampling and monitoring, the degradation effect showed obvious differences: the two experimental groups with cylindrical ferrous sulfate sustained-release materials with a mass ratio of ferrous sulfate to paraffin of 2:3 and 1:1, benzene was completely degraded on the 5th and 7th days of the reaction, respectively. The experimental groups with a ratio of 2:1 and 3:1 almost stopped degrading after the 13th and 15th days, respectively, and the degradation rates of benzene were maintained at 85.1% and 77.8%. The results show that the higher the proportion of ferrous sulfate heptahydrate in the cylindrical ferrous sulfate sustained-release material, the greater the release of Fe 2+ The faster the rate, the more excess Fe 2+ It will compete and consume the free radicals produced by activation, resulting in a decrease in the degradation effect. It also shows that the cylindrical ferrous sulfate sustained-release materials with a mass ratio of ferrous sulfate to paraffin of 2:3 and 1:1 have a better matching activation effect, showing better degradation effect and longer release life.

[0082] The surface of the cylindrical ferrous iron activated persulfate sustained-release material prepared by the present invention is tested and observed before and after release by scanning electron microscopy (SEM).

[0083] Figure 3 Surface microstructure diagram of the cylindrical ferrous sulfate sustained-release material before and after release in Example 1 of the present invention. Figure 3a and b are SEM images of the surface of the cylindrical ferrous sulfate sustained-release material before and after release at 100 times magnification, and c and d are SEM images of the surface before and after release at 500 times magnification. Figure 4 This is a microscopic structure diagram of the material surface of the cylindrical ferrous sulfate sustained-release material before and after release in Example 1 of the present invention. Figure 4 Figures a and b are SEM images of the cylindrical ferrous sulfate sustained-release material before and after release at 100 times magnification, and c and d are SEM images of the cylindrical ferrous sulfate sustained-release material before and after release at 500 times magnification. Figure 3 and Figure 4 It can be seen that the comparative analysis shows that the surface morphology of the sustained-release material has changed significantly before and after release. Before release, the surface of the material is relatively dense, with only a small amount of pores, and the ferrous sulfate and sodium persulfate particles coated in paraffin can be clearly observed under 500 times magnification. After release, obvious pores appeared on the surface of the material, and the ferrous sulfate and sodium persulfate particles coated in paraffin also dissolved and disappeared, indicating that the sustained-release material can effectively release the activator and sodium persulfate in the aqueous solution to degrade organic pollutants in the water.

[0084] The release of ferrous sulfate and sodium persulfate in the sustained-release materials prepared in Examples 1 to 4 and Comparative Example 1 was monitored, and the release data of FeSO4·7H2O and sodium persulfate during the release of the sustained-release materials were fitted using the Bhasker model and the Ritger-Peppas model to study the release mechanisms of the two sustained-release materials.

[0085] Figure 5 The release curve of ferrous sulfate in the sustained-release materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 is shown. Figure 6 The release curve of sodium persulfate in the sustained-release materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 is shown. Figure 5 and Figure 6 The results show that the release rate control step of FeSO4·7H2O in the sustained-release material is internal diffusion, and the release rate control step of sodium persulfate is non-internal diffusion. Compared with the previous research results of Zhu Xueqiang et al., Fe 2+ The presence of the pollutant benzene changes the release mechanism of sodium persulfate in the sustained-release material.

[0086] The Ritger-Peppas model was further used to fit the Figure 7 The release of the cylindrical ferrous sulfate slow-release material FeSO4·7H2O of the present invention is affected by the Fick diffusion inside the matrix. Figure 7The results show that the release of FeSO4·7H2O in the cylindrical ferrous sulfate sustained-release material with a mass ratio of ferrous sulfate to paraffin of 2:3 is affected by Fick diffusion inside the matrix, while the release of FeSO4·7H2O in the cylindrical ferrous sulfate sustained-release material with a mass ratio of ferrous sulfate to paraffin of 1:1, 2:1 and 3:1 is affected by both Fick diffusion inside the matrix and matrix dissolution.

[0087] The slow-release materials prepared in Examples 1 to 4 and Comparative Example 1 were used to simulate the oxidation degradation of benzene and phenanthrene in the aquifer, and the dynamic degradation effect of the slow-release materials was monitored. The specific implementation process is as follows: they are placed in 4 reaction columns with a length of 30 cm, an inner diameter of 3 cm, and an outer diameter of 4 cm, and an additional group of control groups with only cylindrical sodium persulfate slow-release materials (length 4 cm, diameter 2.2 cm) added are set up, and quartz sand (particle size 8 mesh to 70 mesh) is used as a water distribution material. A benzene aqueous solution with a concentration of 30 mg / L and a phenanthrene aqueous solution with a concentration of 1 mg / L are used as test solutions. A peristaltic pump is used to extract the test solution and inject it from the top at a flow rate of (1 mL / min). The actual average flow rate in the column is maintained at 0.602 m / d, and the bottom outlet is sampled regularly. The residual concentration of benzene in the effluent is tested using a gas chromatograph.

[0088] Figure 8 This is a performance diagram of the slow-release materials prepared in Examples 1 to 4 of the present invention and Comparative Example 1 in simulating the oxidation and degradation of benzene and phenanthrene in an aquifer. Figure 8 a in the figure is the performance diagram for degradation of benzene, and b is the performance diagram for degradation of phenanthrene. Figure 8 As shown in the figure, in the column experiment of simulated aquifer, the unactivated cylindrical sodium persulfate slow-release material has poor oxidative degradation effect on benzene and phenanthrene. Among them, the cylindrical ferrous sulfate slow-release material with a mass ratio of ferrous sulfate to paraffin of 1:1 is more efficient in activating the cylindrical sodium persulfate slow-release material, and can more efficiently and stably oxidatively degrade benzene and phenanthrene. It shows that when the slow-release material is applied to aquifer restoration, the cylindrical ferrous sulfate slow-release material prepared by combining the cylindrical ferrous sulfate slow-release material with a mass ratio of ferrous sulfate to paraffin of 1:1 and the cylindrical sodium persulfate slow-release material with a mass ratio of paraffin to sodium persulfate of 2:1 has the best application effect.

[0089] The cylindrical ferrous sulfate activated persulfate slow-release material prepared in Example 1 was used as a filling material for simulating in-situ chemical oxidation remediation of aquifers to construct a permeability reaction barrier and simulate the degradation of benzene in groundwater, wherein the mass ratio of ferrous sulfate to paraffin in the cylindrical ferrous sulfate slow-release material was 1:1; the mass ratio of sodium persulfate to paraffin in the cylindrical sodium persulfate slow-release material was 2:1. The results showed that the slow-release material can maintain an effective degradation effect for up to 20 days. Fig. 9 This is a performance diagram of the slow-release material prepared in Example 1 of the present invention simulating the degradation of benzene in groundwater. Fig. 9Where a is the overall degradation rate of benzene at 5 days, b is the overall degradation rate of benzene at 10 days, and c is the overall degradation rate of benzene at 20 days. Fig. 9 As shown, the overall degradation rates of benzene were 33.04%, 40.34% and 18.65% after 5, 10 and 20 days of operation, respectively, and the degradation effect increased with the increase of the filling material depth. It is confirmed that the slow-release material has the ability to in-situ chemical oxidation remediation of organic contaminated groundwater, and can be used for contaminated groundwater remediation and risk control to prevent pollution rebound.

[0090] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0091] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A ferrous iron activated persulfate sustained-release material, characterized in that: The ferrous sulfate activated persulfate slow-release material comprises a ferrous sulfate slow-release material unit and a persulfate slow-release material unit. Along the length direction of the ferrous sulfate activated persulfate slow-release material, the ferrous sulfate slow-release material unit and the persulfate slow-release material unit are alternately bonded at a mass ratio of 1:1 to 1.5 to obtain the ferrous sulfate activated persulfate slow-release material; wherein the ferrous sulfate slow-release material is formed by mixing and coagulating a first coagulant, ferrous sulfate, citric acid and a first sodium carboxymethyl cellulose, and the persulfate slow-release material is formed by mixing and coagulating a second coagulant, sodium persulfate and a second sodium carboxymethyl cellulose; and the mass ratio of ferrous sulfate, citric acid and sodium persulfate is 1:0.5 to 1:0.15 to 7.

5.

2. The ferrous iron activated persulfate sustained-release material according to claim 1, characterized in that: The mass ratio of ferrous sulfate to the first coagulant is 0.6-3:1, and the mass ratio of the first sodium carboxymethyl cellulose to ferrous sulfate is 1:

100.

3. The ferrous iron activated persulfate sustained-release material according to claim 1, characterized in that: The mass ratio of sodium persulfate to the second coagulant is 0.5-3:1, and the mass ratio of the second sodium carboxymethyl cellulose to sodium persulfate is 1:

100.

4. The ferrous iron activated persulfate sustained-release material according to claim 1, characterized in that: The ferrous sulfate activated persulfate sustained-release material is a cylindrical structure with a diameter of 10 mm to 30 mm. The lengths of the ferrous sulfate sustained-release material unit and the persulfate sustained-release material unit are both 25 mm to 75 mm.

5. The ferrous iron activated persulfate sustained-release material according to claim 1, characterized in that: The first coagulant and the second coagulant are both paraffin wax, the melting point of which is 48°C to 50°C and the density is 0.8 g / cm 3 .

6. The ferrous iron activated persulfate sustained-release material according to claim 1, characterized in that: The particle size of the ferrous sulfate is 100-120 meshes; the particle sizes of the first sodium carboxymethyl cellulose and the second sodium carboxymethyl cellulose are both 100 meshes.

7. A method for preparing the ferrous iron activated persulfate sustained-release material according to any one of claims 1 to 6, characterized in that: The following steps are involved: The first coagulant is heated until it melts, and then ferrous sulfate, citric acid and the first sodium carboxymethyl cellulose are added, mixed evenly, and solidified to obtain a ferrous sulfate sustained-release material unit; The second coagulant is heated until it melts, and then sodium persulfate and the second sodium carboxymethyl cellulose are added, mixed evenly, and solidified to obtain a sodium persulfate sustained-release material unit; The ferrous sulfate slow-release material unit and the sodium persulfate slow-release material unit are alternately bonded by a bonding agent to obtain a ferrous activated persulfate slow-release material.

8. The method for preparing the ferrous iron activated persulfate sustained-release material according to claim 7, characterized in that: The binder is paraffin.

9. Use of the ferrous iron activated persulfate slow-release material according to any one of claims 1 to 6 in in-situ oxidation remediation of groundwater.

Citation Information

Patent Citations

  • Preparation method and application of self-activated persulfate oxidized medicament

    CN104071886A

  • Ferrous activation persulfate slow-release candle for underground water in-situ oxidation restoration

    CN106477709A

  • Preparation method and applications of ferrous sulfide / biological carbon composite material

    CN106966456A

  • Persulfate activating system, method for degrading pollutant, and application

    CN109133321A

  • Phenanthrene-contaminated soil remediation agent and preparation method thereof

    CN115044380A